Using an online Learning Management System to personalise learning for primary students : a descriptive multiple case study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University, Manawatū, New Zealand - Edmunds, Bronwyn (Massey University, 2013)
Personalising learning, digital technologies and Learning Management Systems are ‘hot topics’ in education in 2013. Learning Management Systems, hereafter referred to as an LMS, can personalise learning by encouraging teaching approaches that hold the student at the centre of the learning process (Seiler, as cited in Interface Magazine, 2009). However, there is little accessible research about how the LMS has been utilised in schools (Watson & Watson, 2007), especially primary schools, with some educators questioning the role that the LMS has to play in today’s schools (Downes, 2005; McLoughlin & Lee, 2008). This descriptive multiple-case study set out to explore the role of an LMS in personalising learning for students from the perspective of three primary school teachers. The intention was to provide insight into the role an LMS could play in classrooms when personalising learning. However, it became more about exploring the components of personalising learning and how this transferred into the LMS. The research project involved gathering multiple sources of data from interviews, observations and documentary information from the LMS. The findings from this research suggest that an LMS has the potential to be a key part of a primary classroom environment which is built on the components of personalising learning. The degree to which personalising learning occurs is dependent on the teacher’s overriding pedagogy, knowledge and understanding of personalising learning, school constraints and the perceived capacity of students to be independent learners. For the teachers in this project, personalising learning involved: (a) learning built around assessment for learning pedagogy, (b) a highly-structured approach to learning and teaching that places the needs and interests of students at the centre of learning, (c) learners informed and empowered through student choice and student voice, (d) a core curriculum of literacy and maths and (e) KnowledgeNET (the LMS at the centre of this study) as a tool to support learning. The findings highlight the interconnected nature of personalising learning pedagogy, an LMS and classroom practice.
Keywords: Learning Management System; Primary school teaching; Personalised learning; Individualised instruction